1991
DOI: 10.1002/1097-0142(19910115)67:2<398::aid-cncr2820670214>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Second cancer after radiation therapy for cancer of the uterine cervix

Abstract: Radiation-induced cancers after radiation therapy for cancer of the uterine cervix were investigated on 11,855 patients including 5725 patients treated with radiation therapy alone, 1969 postoperative radiation therapy and 4161 surgery alone. The observed-to-expected ratios of the second primary cancer was 0.933 for the patients with radiation therapy alone and 1.074 for the patients with postoperative radiation therapy, respectively. No significant increase was observed in the risk of second primary cancers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 16 publications
0
34
0
3
Order By: Relevance
“…Arai et al analyzed 11,855 patients with cervical cancer in four institutions from 1961 to 1981 and did not find an elevated risk for either the radiation or surgery group when all sites were combined. However, when evaluated on a site-by-site base, significant elevation of risk was found for rectal, lung, bladder, and leukemia cancer in the radiation group, and lung cancer only for the surgery group [17]. In the present study, we analyzed the incidence and risk of second primary cancers using a population-based cohort of 52,972 patients with an initial diagnosis of cervical cancer between 1979 and 2008 in Taiwan.…”
Section: Introductionmentioning
confidence: 73%
“…Arai et al analyzed 11,855 patients with cervical cancer in four institutions from 1961 to 1981 and did not find an elevated risk for either the radiation or surgery group when all sites were combined. However, when evaluated on a site-by-site base, significant elevation of risk was found for rectal, lung, bladder, and leukemia cancer in the radiation group, and lung cancer only for the surgery group [17]. In the present study, we analyzed the incidence and risk of second primary cancers using a population-based cohort of 52,972 patients with an initial diagnosis of cervical cancer between 1979 and 2008 in Taiwan.…”
Section: Introductionmentioning
confidence: 73%
“…They found an increased risk for cancers of the bladder, rectum, vagina, and caecum. Arai et al (1991) reported significantly higher incidences of second cancers in the rectum, bladder, and lung as well as leukaemia. Kleinerman et al (1995) described a large-scale study of 49 828 patients with cervical cancer treated with radiation therapy and 16 713 matched patients treated without radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This follows the pattern for radiation-induced SPM but has not been shown by other groups ( I , 4, 20,23,24). It is of interest to compare this finding with results from the evaluation of the Radiumhemmet series of carcinoma of the cervix treated in 1914-1965 (21).…”
Section: Cervical Cancermentioning
confidence: 99%